L’enargeia musicale ou les modalités d’une ut musica poesis dans The Arte of English Poesie de George Puttenham (1589) - Laïla Ghermani (Etudes Epistémè)
Puttenham’s Arte of English Poesie is unique, for it is a poetic art which conceives and defines poetry as a musical art. In the wake of the numerous apologies of vernacular poetry in Europe, its author aims at demonstrating the aptness of the English language to poetry and especially its genial affinities with music. Puttenham makes use of all the knowledge available at his time to write his treatise and he especially refers to the debate opposing quantitative verse and stressed verse. The status of poetry remains however uncertain, oscillating between a musical expression related to the music of the spheres and rhetoric, but it finds a unity in the paradoxical concept of musical enargeia, an auditory representation equal to a visual representation. The second remarkable paradox pertains to the practical character of the musical poetry described by Puttenham. In fact, his poetic art does not have a purely aesthetic or epistemological purpose but is intended to help the courtiers acquire a comely musical varnish in order to favour their progress in the social hierarchy.